Anal canal condyloma acuminatum treated with anti-HPV biological dressing: Clinical analysis of 64 cases - Yanyan Hu; Meihua Li; Jing Liu; Qian Huang; Jinbo Chen; Liuqing Chen; Dongsheng Li (Wolters Kluwer Medknow Publications, 2022)
Background: Anal canal condyloma acuminatum (CA) is a refractory disease with a high recurrence rate caused by human papillomavirus (HPV). Multiple clinical trials demonstrate that anti-HPV biological dressing is safe and effective in treating HPV infection, which has been used in treating high-risk HPV-positive and cervical intraepithelial neoplasia I (CIN I) patients. Yet, there is still a lack of clinical data for the treatment of anal canal CA. Aims and Objectives: To evaluate the clinical efficacy and application value of anti-HPV biological dressing in anal canal CA. Materials and Methods: Taken currently recommended treatment 5-aminolevulinic acid-mediated photodynamic therapy (ALA-PDT) as a positive control, 128 patients were included with 64 in each group, and a prospective, randomized, positive controlled, non-inferiority clinical trial was conducted. After removing visible skin lesions with conventional microwave, the treatment group was given anti-HPV biological dressing, while the control group received the conventional ALA-PDT treatment. Patients were followed up on the 1st, 12th and 24th weeks after the treatment. The cure rate, recurrence rate, HPV-negative conversion rate, and adverse events were recorded. Results: In the 1st, 12th and 24th weeks after treatment, the cure rate, recurrence rate and HPV-negative conversion rate of the treatment group and the control group showed no statistically significant difference. In the treatment group, 56 patients developed transient mild itching and all were relieved spontaneously, while in the control group, most of the patients experienced obvious pain and some patients needed symptomatic treatment. No severe systemic adverse events were observed. Conclusion: Compared with ALA-PDT, topical application of anti-HPV biological dressing has comparable promising outcomes in the treatment of anal canal CA, with fewer side effects and simpler operation making it suitable for clinical applications.